A HOTAIR regulatory element modulates glioma cell sensitivity to temozolomide through long-range regulation of multiple target genes - Zhang, Lei; He, Anshun; Chen, Bohan; Bi, Jinfang; Chen, Jun; Guo, Dianhao; Qian, Yuyang; Wang, Wenbin; Shi, Tengfei; Zhao, Zhongfang; Shi, Jiandang; An, Woojin; et al. (Genome Research, 2020)
Temozolomide (TMZ) is a frequently used chemotherapy for glioma; however, chemoresistance is a major problem limiting its effectiveness. Thus, knowledge of mechanisms underlying this outcome could improve patient prognosis. Here, we report that deletion of a regulatory element in the HOTAIR locus increases glioma cell sensitivity to TMZ and alters transcription of multiple genes. Analysis of a combination of RNA-seq, Capture Hi-C, and patient survival data suggests that CALCOCO1 and ZC3H10 are target genes repressed by the HOTAIR regulatory element and that both function in regulating glioma cell sensitivity to TMZ. Rescue experiments and 3C data confirmed this hypothesis. We propose a new regulatory mechanism governing glioma cell TMZ sensitivity.